Technology-Mediated Realistic Mathematics Education and the Bridge21 Model: A teaching experiment - Oldham, Elizabeth; Tangney, Brendan; Bray, Aibhin (Charles University in Prague, Faculty of Education and ERME, 2015)
Many recent curriculum reforms aim to address shortfalls with regard to student engagement with mathematics by harnessing the affordances of technology, social constructivist pedagogies, contextual scenarios, and/ or approaches aligned with Realistic Mathematics Education (RME). However, these may not sit well within a conventional classroom setting; a 21st Century (21C) learning model may be more appropriate. This paper describes a teaching experiment in Ireland, supporting an ongoing curriculum reform; it used technology-mediated activities consonant with social constructivism, RME, and 21C learning. The study involved twenty students (aged 15–17) over a two-day period. Results suggest that the approach has the potential to increase student engagement with and confidence in mathematics
Proceedings of the 9th Congress of European Research in Mathematics Education
PUBLISHED
Prague, Czech Republic
Keywords: RME; Contextualised learning; Twenty-first century learning; Technology-mediated; Post-primary education; Mathematics Education